2018
DOI: 10.33899/mmed.2018.159190
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute otitis media among children in Mosul

Abstract: Context: Acute otitis media (AOM) is the most frequent diagnosis in the children visiting offices. The prolonged and recurrent episodes of AOM may lead to hearing impairment and delayed speech development, which will influence the child's performance at school. Aim: The aim of this study is to identify the risk factors of acute otitis media in preschool children attending ENT clinics at Al-jamhory Teaching Hospital in Mosul. Methods: To achieve this aim, a case control study design was adopted. The sample of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…AOM is caused by a virus or by bacteria and rarely fungi [2,5]. In terms of gender, there was a predominance of male (58.8%) compared with female (41.2%) infants with AOM which was agreed with several previous studies [31,32]. However, Stangerup [33] and Zhang [34] have shown that no gender differences were found in the incidence of AOM.…”
Section: Discussionsupporting
confidence: 86%
“…AOM is caused by a virus or by bacteria and rarely fungi [2,5]. In terms of gender, there was a predominance of male (58.8%) compared with female (41.2%) infants with AOM which was agreed with several previous studies [31,32]. However, Stangerup [33] and Zhang [34] have shown that no gender differences were found in the incidence of AOM.…”
Section: Discussionsupporting
confidence: 86%